PEMBUATAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROJECT DENGAN HYBRID LEARNING UNTUK PENGUATAN PROFIL PELAJAR PANCASILA - Sumarmi Sumarmi; Neni Wahyuningtyas; Alfyananda Kurnia Putra; Tuti Mutia; Bayu Wijayanto (Universitas Negeri Malang, 2023)
PROJECT-BASED STUDENTS WORKSHEET TO ENHANCE STUDENTS' PANCASILA PROFILE IN HYBRID LEARNINGThe COVID-19 pandemic has had a changing impact on various aspects of life. One of them is the aspect of education which so far tends to be carried out in a conventional classical manner, which must develop towards digitalization. Therefore, this article discusses community service with the aim of improving the skills of teachers in schools under the auspices of YPK East Java in making project-based worksheets with hybrid learning to strengthen the profile of Pancasila students. The method adopted is empowerment through training and mentoring for teachers in schools under the auspices of YPK East Java with three stages namely preparation, implementation and follow-up. Based on an analytical study, the results of community service activities showed a positive impact on improving the skills of teachers in schools under the auspices of YPK East Java in making project-based worksheets with hybrid learning. Thus, teachers in schools have skills in implementing learning that is able to support strengthening the profile of Pancasila students.Pandemi COVID-19 memberikan dampak perubahan pada berbagai aspek kehidupan. Salah satunya yaitu aspek pendidikan yang selama ini cenderung dilaksanakan secara klasikal konvensional harus berkembang ke arah digitalisasi. Oleh karena itu, artikel ini membahas tentang pengabdian masyarakat dengan tujuan meningkatkan keterampilan guru-guru di sekolah yang ada di bawah naungan YPK Jatim dalam pembuatan LKPD berbasis project dengan hybrid learning untuk penguatan profil pelajar Pancasila. Metode yang ditempuh yaitu pemberdayaan melalui pelatihan dan pendampingan pada guru-guru di sekolah yang ada di bawah naungan YPK Jatim dengan tiga tahapan yaitu persiapan, pelaksanaan, dan tindak lanjut. Berdasarkan kajian analisis, hasil kegiatan pengabdian kepada masyarakat menunjukkan dampak positif pada peningkatan keterampilan guru di sekolah yang ada dibawah naungan YPK Jatim dalam membuat LKPD berbasis project dengan hybrid learning. Sehingga, guru di sekolah mempunyai ketrampilan dalam mengimplementasikan pembelajaran yang mampu mendukung penguatan profil pelajar Pancasila.